First 10 years of journal "Morphologia": analysis of activities. - Tverdokhleb, I. V.; Pototskaya, O. Yu. (Морфологія / Morphologia / Morfologìâ, 2017)
Scientometric databases represent a good possibility to evaluate the objective parameters of scientific journals activity. Journal “Morphologia” has been registered in Russian index of scientific citation since 2009 and providing an opportunity to analyse wide spectrum of its indexes for the period of 8 years. One of the most well-known scientometric parameter is the impact-factor (IF); two-eyar IF demonstrates the tendency to growth up to the 2011 and after оscillations return to the same value in 2015. Five-year IF also demonstrates uncertain tendency with the highest value in 2013 (0.213 without self-citation) and in 2015 it reaches the level of 0.161. The same changes are characteral for the total number of citation per one year: in 2013 it was registered the highest value - 67 (without self-citation), while in 2015 it decreased to 59. Distribution of the citation among different journals could be measured by the Herfindahl index; continuous decrease of this paremeter up to the level 339 evidence rather uniform distribution of citations among 145 journals. Comparison of these scientometric parameters with another ukrainian journals of the same scientific field revealed that “Morphologia” occupy the leader position among another morphological periodicals. Taken together these data evidence the importance of scientometric databases and their indexes for the objective comparison of scientific journals.